An enigmatic and large-seize specimen of Panochthus (Glyptodontidae, "Panochthini") from the Ensenadan (Early-Middle Pleistocene) of the Pampean region, Argentina - Zamorano, Martín (2013)
Panochthus Burmeister (Mammalia, Xenarthra, Glyptodontidae) is one of the best characterized Pleistocene genera. It is possible to recognize 2 Ensenadan (Early-Middle Pleistocene) species from the Pampean region of Argentina and Bolivia, Panochthus intermedius Lydekker and P. subintermedius Castellanos, whereas 2 species are considered as valid for the age Bonaerian-Lujanian (Middle Pleistocene-Late Pleistocene), namely P. tuberculatus Owen and P. frenzelianus Ameghino. This paper provides the first record of a skull belonging to Panochthus from Ensenadan deposits in the Pampean Region of Argentina, being the second record for the genus in this lapse. The synapomorphies that support this taxonomic interpretation are: a frontal-ventrally inclined nasal zone forming a 45º angle between the palate plane and the plane of the upper rostral zone; a cranial length/height ratio that less than 1½ of the height, without considering the descending processes of the zygomatic arch; external nasal openings with a fronto-ventral orientation. A comparative study with P. intermedius and other species from the Bonaerian-Lujanian refutes its placement among any of these; on the other hand, no cranial materials are known for the other species from the Ensenadan (P. subintermedius). Considering that the former is a large species, and that this skull corresponds undoubtedly to a species of Panochthus of large dimensions, the most parsimonious taxonomic hypothesis is to tentatively assign the material MLP 84-IX-2-11 to Panochthus cf. subintermedius. Future findings of more complete materials would provide support or refute this hypothesis.